Reduced FOXF1 links unrepaired DNA damage to pulmonary arterial hypertension - Sarasa Isobe; Ramesh V. Nair; Helen Y. Kang; Lingli Wang; Jan-Renier Moonen; Tsutomu Shinohara; Aiqin Cao; Shalina Taylor; Shoichiro Otsuki; David P. Marciano; Rebecca L. Harper; Mir S. Adil; et al. (Nature Communications, 2023)
Abstract Pulmonary arterial hypertension (PAH) is a progressive disease in which pulmonary arterial (PA) endothelial cell (EC) dysfunction is associated with unrepaired DNA damage. BMPR2 is the most common genetic cause of PAH. We report that human PAEC with reduced BMPR2 have persistent DNA damage in room air after hypoxia (reoxygenation), as do mice with EC-specific deletion of Bmpr2 (EC-Bmpr2 -/-) and persistent pulmonary hypertension. Similar findings are observed in PAEC with loss of the DNA damage sensor ATM, and in mice with Atm deleted in EC (EC-Atm -/-). Gene expression analysis of EC-Atm -/- and EC-Bmpr2 -/- lung EC reveals reduced Foxf1, a transcription factor with selectivity for lung EC. Reducing FOXF1 in control PAEC induces DNA damage and impaired angiogenesis whereas transfection of FOXF1 in PAH PAEC repairs DNA damage and restores angiogenesis. Lung EC targeted delivery of Foxf1 to reoxygenated EC-Bmpr2 -/- mice repairs DNA damage, induces angiogenesis and reverses pulmonary hypertension.